2019
DOI: 10.17712/nsj.2019.4.20190027
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of patients with multiple sclerosis in Saudi Arabia regarding the relationship between smoking and multiple sclerosis

Abstract: Objectives: To assess the awareness of patients with multiple sclerosis about the relationship between smoking and multiple sclerosis in Saudi Arabia. Methods: A descriptive cross-sectional study was carried out in 2018 for 162 patients who are attending a tertiary hospital in Jeddah, Kingdom of Saudi Arabia. Self-administered questionnaire and telephone-based interview were used to collect the data. The Analysis was carried out through a statistical package for the social sciences)SPSS(software version 21 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Our study showed that most PwMS do not know their disease phenotype, which is similar to what another study done in Jeddah reported [ 16 ]. This could reflect a lack of patient awareness of their disease or a lack of effective communication and education by physicians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that most PwMS do not know their disease phenotype, which is similar to what another study done in Jeddah reported [ 16 ]. This could reflect a lack of patient awareness of their disease or a lack of effective communication and education by physicians.…”
Section: Discussionsupporting
confidence: 90%
“…A study investigating awareness of smoking risk among PwMS in Jeddah also showed a high prevalence of active smokers (34.6%). It was also shown that most patients did not know whether smoking is a risk factor for MS or disagreed to this [ 16 ]. All of this shows that, indeed, smoking is prevalent among PwMS and can be a strong risk factor for the disease in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results showed extremely low levels of awareness of adverse effects of smoking and passive smoking on MS onset, progression and treatment in our sample. This lack of knowledge of a modifiable risk factor represents a failing in caring for people with MS, and is consistent with other studies 12–14. There is an urgent need for remedial education and action to ensure better promotion of smoking cessation as an integral part of MS care.…”
Section: Discussionsupporting
confidence: 79%
“…Evidence is emerging that people with MS are largely unaware of the risks of smoking to MS, and that there are MS-specific barriers to quitting, such as the potential impact of cessation-induced stress on MS 12–14. Our qualitative work also identified several MS-specific barriers to smoking cessation, including concerns that quitting may negatively impact MS symptoms, such as mood, cognition, pain and relapses 14.…”
Section: Introductionmentioning
confidence: 91%
“…We appreciate your interest and comment on our recent study. 1 Your letter raised important factors that could lead to bias in any study related to multiple sclerosis (MS) patients. Mood disorder and fatigue are common among MS patients.…”
Section: Reply From the Authormentioning
confidence: 99%